2020
DOI: 10.1055/a-1127-3170
|View full text |Cite
|
Sign up to set email alerts
|

A prospective, randomized trial of thrombin versus cyanoacrylate injection in the control of acute gastric variceal hemorrhage

Abstract: Background Acute gastric variceal hemorrhage (AGVH) is a serious complication of portal hypertension. Endoscopic cyanoacrylate glue injection is standard therapy for acute hemostasis; however, it may be associated with serious complications. The role of thrombin injection has not been confirmed. This study compared endoscopic thrombin and glue injections in the hemostasis of AGVH. Methods 68 eligible patients with AGVH were randomized to receive thrombin injection (33 patients) or glue injection (3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 24 publications
0
33
0
1
Order By: Relevance
“…Even though thrombin treatment was found beneficial in controlling bleeding from GV, especially Type 2 GOV in small single-center series, high-quality studies were lacking [ 40 43 ]. Recently, Lo and colleagues, in a prospective randomized trial, showed that endoscopic thrombin injection was similar to glue injection in achieving successful haemostasis of acute GV bleeding but with higher incidence of complications associated with the latter [ 44 ]. Few reports demonstrating the use of inorganic absorbent powder TC-325 haemostatic spray (Hemospray®, Cook Medical, IN, USA) in patients with refractory gastric variceal bleeding after the failure of glue injection therapy has been published in the literature.…”
Section: Treatmentmentioning
confidence: 99%
“…Even though thrombin treatment was found beneficial in controlling bleeding from GV, especially Type 2 GOV in small single-center series, high-quality studies were lacking [ 40 43 ]. Recently, Lo and colleagues, in a prospective randomized trial, showed that endoscopic thrombin injection was similar to glue injection in achieving successful haemostasis of acute GV bleeding but with higher incidence of complications associated with the latter [ 44 ]. Few reports demonstrating the use of inorganic absorbent powder TC-325 haemostatic spray (Hemospray®, Cook Medical, IN, USA) in patients with refractory gastric variceal bleeding after the failure of glue injection therapy has been published in the literature.…”
Section: Treatmentmentioning
confidence: 99%
“…In an only RCT available which compares thrombin to cyanoacrylate injection in the control of AGVH, thrombin injection and glue injection had similar success rate (90% vs. 90.9%). However, a higher incidence of complications (51% vs. 12%) and ulcers (37% vs. 0%) were noted with glue injection as compared to thrombin [36]. Results of this study cannot be generalized as the sample size used in this study was small.…”
Section: Thrombin Injectionmentioning
confidence: 74%
“…Lo et al [ 34 ] recently reported on the first prospective randomised trial of thrombin versus cyanoacrylate in acute gastric variceal haemorrhage. 33 patients were randomised to the thrombin arm with 35 randomised to glue injection; the primary outcome was the development of injection-induced gastric ulceration.…”
Section: Discussionmentioning
confidence: 99%